Association of autism spectrum disorder with epilepsy and abnormal electroencephalogram in children - Rashid, Farzana Binta; Sumi, Sufia Khatun; Parvin, Jobaida; Mistry, Banita; Ara Begum, Mosammat Shameem; Islam, Ariful; Saha, Narayan (International Journal of Contemporary Pediatrics, 2024)
Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by various brain abnormalities, although its exact cause remains unknown. Epilepsy is commonly associated with ASD, and children with ASD often exhibit paroxysmal EEG abnormalities, even without clinical seizures. Both ASD and epilepsy have a significant impact on a child’s well-being and contribute to the burden on the family. This study aimed to assess the association of autism spectrum disorder with epilepsy and abnormal electroencephalogram in children. Methods: This comparative cross-sectional study was conducted in the outpatient Department of Pediatric Neurology, National Institute of Neurosciences (NINS), Dhaka, Bangladesh from January 2021 to July 2022. The study included a total of 60 children aged 31 months to 14 years diagnosed with autism spectrum disorder (ASD) at the pediatric outpatient department (OPD) in NINS, selected purposively. Data analysis was performed using the SPSS version 25.0 program. Results: In the ASD with epilepsy group, 50% of children had moderate ASD, and 50% had high ASD. In the ASD with abnormal EEG group, 66.67% had high ASD, and 33.33% had moderate ASD. In the ASD-only group, 81.25% had moderate ASD, 12.5% had high ASD, and 6.25% had low ASD. When comparing these groups with their corresponding comparison groups, the ASD with abnormal EEG group exhibited significantly more severe autism than children with ASD and normal EEG (p<0.001). Conversely, the ASD-only group had less severe autism than children with ASD and epilepsy/abnormal EEG (p<0.001). Conclusion: Children with ASD and abnormal EEG had a higher severity of autism, with 66.67% categorized as high severity. In contrast, children with ASD only experienced less severe autism, with 81.25% categorized as moderate. This indicates that ASD-only children tend to have a milder presentation of autism compared to those with ASD and comorbid epilepsy or abnormal EEG.